Propagaç\~ao assimétrica de choques monetários na economia brasileira: Evidências com base em um modelo vetorial n\~ao linear de transiç\~ao suave - Vinícius dos Santos Cerqueira; Márcio Bruno Ribeiro; Thiago Sevilhano Martinez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper attempts to extend empirical investigations about the asymmetric effects of monetary shocks in the Brazilian economy. We specify and estimate a nonlinear smooth transition vector autoregressive model including output, price level, exchange rate and a monetary policy indicator (Selic rate). Impulse response functions showed that positive and negative monetary shocks have asymmetric effects on output growth and inflation. Regarding to the business cycle, contractionary monetary shocks showed stronger effects in low-growth states while expansionary shocks were stronger in highergrowth periods. In addition, we found that inflation and output growth are rigid to countercyclical monetary shocks.
Keywords: E32; E52; C32; C52; 330; Geldpolitik; Wirkungsanalyse; Brasilien